5.8 CHARACTERISTICS OF PERSONALITY IN SOCIAL RELATIONSHIPS - 1. Salimov Bakhriddin Lutfullaevich. Professor at Tashkent State Transport University. 2. Raxmatov Umid Ravshan o‘g‘li. Student at Tashkent State Transport University. (Innovative technologies in construction Scientific Journal, 2024)
Аnnotation If there were no such features as science, knowledge and enlightenment, there would be no civilizations of mankind. Abu Ali ibn Sina also wrote down remarkable thoughts on this topic. In the views of most scholars and philosophical teachings, in the struggle between good and evil in society, it is said to respond to evil with good. In particular, the thoughts of Abulqasim Firdavsi, the great creator of the Eastern world, can be a clear example of this.